'Don't Say It's Going to Be Okay': How International Educators Embrace Transformative Education to Support Their Students Navigating Our Global Climate Emergency - Jeremy Jimenez; Laura Moorhead (MDPI AG, 2021)
Many education professionals are looking to Environmental and Sustainability Education as a guide to incorporate curricular lessons and activities into school classrooms and other learning environments. Building upon the framework of Jickling and Wals (2008) of identifying how to teach about environmental education in transformative ways, this study examined how the experiences and perspectives of seven faculty and staff members at a K-12 International Baccalaureate school in Singapore impacted how they taught about sustainability issues. It also investigated how they work to empower students to become change agents by employing concepts and strategies such as hands-on learning, systems thinking, and service learning. Qualitative interview data revealed four overarching key themes: (1) importance of local context (both the school and the broader socio-political context), (2) pedagogy in relation to student psychology, (3) teacher and staff views on effective pedagogy for teaching about climate crises, and (4) mental health, as experienced by both students and their educators. Teachers and their students regularly struggled with tensions of authority (e.g., school/government, parent/child, teacher/student) and outlook (e.g., "doomism"/hope, empowered/disempowered). Nonetheless, they expressed a variety of thoughtful ways to cultivate their students' lifelong advocacy for the environment and other related social justice issues.